Physician-Hastened-Death in Patients with Progressive Neurodegenerative or Neuromuscular Disorders - Russell, James A. (Seminars in Neurology, 2018)
Physician-hastened-death remains a controversial topic for patients and those who care for them. It is a particularly relevant topic for neurologists who currently, or will in the future, reside in jurisdictions where physician-hastened-death is legal. In this article, I attempt to provide a comprehensive and contemporary discussion of hastened-death issues in a measured and respectful fashion. My goal is to provide clinicians with the information necessary to mold their own judgment and conscience in preparation for a time in which one or more of their patients request their participation in physician-hastened-death.
Keywords: lawful physician-hastened-death; physician-assisted suicide; fiduciary; professionalism; euthanasia